Convergence Patterns in Financial Development: Evidence From Club Convergence - Apergis, Nicholas; Christou, C.; Miller, S. (Physica-Verlag GmbH und Co., 2012)
This article analyzes the degree of convergence of financial development for a panel of 50 countries. We apply the methodology of Phillips and Sul (Econometrica 75:1771–1855, 2007) to various indicators of financial development to assess the existence of convergence clubs. We consider ten alternative indicators of financial development that various researchers use to proxy for the degree of financial development in countries. Overall, the results do not support the hypothesis that all countries converge to a single equilibrium state in financial development. Nevertheless, strong evidence exists of club convergence. Countries demonstrate a high degree of convergence in the sense that in the majority of financial indexes they form only two or three convergence clubs, depending on the measure of financial development used. We also apply the Phillips and Sul method to two real variables, per capita output and fixed capital investment to GDP, and find strong evidence of five and four distinct convergence clubs, respectively. Finally, we compare the various convergence clubs associated with financial development indicators to those clubs for per capita output and fixed capital investment to GDP. We conclude that strong evidence supports the correspondence between the convergence clubs for financial development and those two real variables.